The effects of endocrine‐disrupting chemicals on ovarian‐ and ovulation‐related fertility outcomes - Land, Katie L.; Miller, Frances G.; Fugate, Ava C.; Hannon, Patrick R. (Molecular reproduction and development, 2022)
Exposure to endocrine‐disrupting chemicals (EDCs) is unavoidable, which represents a public health concern given the ability of EDCs to target the ovary. However, there is a large gap in the knowledge about the impact of EDCs on ovarian function, including the process of ovulation. Defects in ovulation are the leading cause of infertility in women, and EDC exposures are contributing to the prevalence of infertility. Thus, investigating the effects of EDCs on the ovary and ovulation is an emerging area for research and is the focus of this review. The effects of EDCs on gametogenesis, uterine function, embryonic development, and other aspects of fertility are not addressed to focus on ovarian‐ and ovulation‐related fertility issues. Herein, findings from epidemiological and basic science studies are summarized for several EDCs, including phthalates, bisphenols, per‐ and poly‐fluoroalkyl substances, flame retardants, parabens, and triclosan. Epidemiological literature suggests that exposure is associated with impaired fecundity and in vitro fertilization outcomes (decreased egg yield, pregnancies, and births), while basic science literature reports altered ovarian follicle and corpora lutea numbers, altered hormone levels, and impaired ovulatory processes. Future directions include identification of the mechanisms by which EDCs disrupt ovulation leading to infertility, especially in women.